1993
DOI: 10.1101/gad.7.7a.1176
|View full text |Cite
|
Sign up to set email alerts
|

A small nucleolar RNA is processed from an intron of the human gene encoding ribosomal protein S3.

Abstract: A human small nucleolar RNA, identified previously in HeLa cells by anti-fibrillarin autoantibody precipitation and termed RNA X, has been characterized. It comprises two uridine-rich variants (148 and 146 nucleotides}, which we refer to as snRNA U15A and U15B. Secondary structure models predict for both variants a U15-specific stem-loop structure, as well as a new structural motif that contains conserved sequences and can also be recognized in the other fibrillarin-associated nucleolar snRNAs, U3, U14, and RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
146
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(152 citation statements)
references
References 58 publications
5
146
0
1
Order By: Relevance
“…This peculiar mechanism has been demonstrated to be involved also in the production of the other snoRNAs recently found to be encoded in introns, U14, U15 U16 and HeLa U17 RNAs (7)(8)(9)41). In the case of U16 RNA, encoded in an intron of the Xenopus gene for r-protein L1, it has been shown that its production is alternative to that of the mature Li mRNA (8).…”
Section: Discussionmentioning
confidence: 99%
“…This peculiar mechanism has been demonstrated to be involved also in the production of the other snoRNAs recently found to be encoded in introns, U14, U15 U16 and HeLa U17 RNAs (7)(8)(9)41). In the case of U16 RNA, encoded in an intron of the Xenopus gene for r-protein L1, it has been shown that its production is alternative to that of the mature Li mRNA (8).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this helix in accu mulation of a yeast ACA snoRNA, snRl 1, has been dem onstrated (Balakin et al 1996). Interestingly, many box C/D snoRNAs feature a stem structure similar to helix II (Tycowski et al 1993;Watkins et al 1996). Although this helix is dispensable for the accumulation of U14 snoRNA, it has been implicated in the processing of box C/D snoRNAs, which lack a 5',3' terminal stem struc ture (helix I) (Watkins et al 1996).…”
Section: Genes and Developmentmentioning
confidence: 99%
“…Accumulating evidence suggests that excision of intronic snoRNAs relies on exonucleolytic activities Filipowicz 1993, 1995;Xia et al 1997). The C, D, and ACA boxes of snoRNAs have been postulated to bind putative protein factor(s) which could delineate the terminal boundaries by protecting the snoRNAs from exonucleolytic degradation (Huang et al 1992;Tycowski et al 1993;Balakin et al 1994Balakin et al , 1996Caffarelli et al 1996;Watkins et al 1996;Xia et al 1997).…”
Section: The Two Major Classes Of Snornas Show Intriguing Similaritiesmentioning
confidence: 99%
See 2 more Smart Citations